Penerapan Model Kooperatif Learning Tipe Jigsaw Meningkatkan Keterampilan Sosial dan Minat Belajar Siswa Kelas IV Mata Pelajaran Pendidikan Agama Katolik - Anugrah Steven Doloksaribu; Din Oloan Sihotang (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2025)
This study aims to enhance the social skills and learning interest of fourth-grade students through the implementation of the Cooperative Learning Model of the Jigsaw Type in the subject of Catholic Religious Education at Santo Daniel Elementary School in Batu Mbelin. Based on the classroom action research approach, this study was conducted in two cycles involving 13 students as the main subjects. The first cycle involved planning, action, observation, and reflection, followed by evaluation and improvement for the second cycle. The results of the first cycle indicated that the average percentage of students' social skills and learning interest had not yet reached the established success standards. However, after implementing improvements in the second cycle, the results showed a significant increase in students' social skills and learning interest. The average percentage of social skills reached 92.1%, while learning interest reached 94.0%, both categorized as "Very Good." The implications of this study are that the cooperative learning model of the jigsaw type can effectively enhance students' social skills and learning interest, providing a positive contribution to curriculum development and learning strategies at the elementary school level.